OP34 Universal antenatal culture-based screening for maternal group b streptococcus (gbs) carriage to prevent early-onset gbs disease: a systematic review for the uk national screening committee (nsc). (2nd September 2017) - Seedat, F; Geppert, J; Stinton, C; Patterson, J; Brown, CS; Tan, B; Freeman, K; Uthman, OA; McCarthy, ND; Robinson, ER; Johnson, SA; Fraser, H; et al.
Abstract : Background: GBS is the leading cause of morbidity and mortality from neonatal sepsis in the UK and patient groups are keen for screening to be implemented. Intrapartum antibiotic prophylaxis (IAP) is offered to women identified with GBS carriage or GBS risk factors to prevent mother to baby transmission and early-onset GBS disease (EOGBS, <7 days). This review on universal GBS screening for pregnant women was undertaken to assist NSC policy decision-making. Review questions were on: epidemiology of GBS, diagnostic accuracy of tests, effectiveness of IAP treatment, and effectiveness of universal GBS screening. Methods: Medline, Embase, and Cochrane databases were searched. Grey literature included Public Health England, British Paediatric Surveillance Unit, Audits and Confidential Enquiries, and reference lists of included papers. Participants were pregnant women≥35 weeks or neonates<7 days. The intervention was selective culture from recto-vaginal swabs at 35–37 weeks followed by IAP treatment for those who were culture positive. Reviewers independently screened records, extracted data, and assessed methodological quality using appropriate tools for each question, including QUADAS-2, Cochrane RoB, and RoBANS tools. Data were synthesised narratively. Results: 73 studies were included from 6287 references. EOGBS in the UK affects 0.57 per 1000 live births with a case fatality of 5.2%. Twenty-two percent of EOGBS cases and 63% of deaths are in preterm births (many would be ineligible for screening). The natural history of GBS is not known. We estimate that universal GBS screening would be offered to approximately 7 18 126 pregnant term women annually.Approximately 63 347 (57.7%) women who test positive in labour and 3282 (8%) who test negative in labour would transmit GBS to their neonates, and approximately 350 (0.5%) neonates would develop EOGBS. We estimate the positive predictive value of selective culture to detect EOGBS to be around 0.2% (350/150, 806). More than 1 50 450 (>99%) women would be false positive and unnecessarily treated. Harms from IAP are unclear but will include antibiotic resistance and other possible health problems. There were no randomised controlled trials of the effectiveness of GBS screening and observational studies gave inconsistent results for EOGBS mortality and morbidity. Conclusion: EOGBS is an important health condition. However, tests are not accurate predictors of maternal GBS transmission, or of EOGBS. Evidence on the harms and benefits of GBS screening is limited. Universal screening is therefore not recommended.